A Civic Resignation?: Generational Reactions to Government Data Breaches in Indonesia - Hadi, Irnasya S (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2025)
This paper examines how different generations in Indonesia perceive and respond to government data breaches, a recurring phenomenon that undermines trust in state-led digital governance. Using a mixed-methods design, it draws on interviews with civil society organisations, focus groups, and a survey of 1,081 respondents across Baby Boomers, Generation X, Millennials, and Generation Z. Findings show that distrust in the government’s ability to protect personal data is widespread, but generationally stratified. Baby Boomers and Generation X largely treat breaches as bureaucratic inevitabilities, exhibiting high resignation and minimal engagement. In contrast, Millennials and Generation Z show stronger concern, digital literacy, and proactive behaviour, yet frequently cycle through outrage and advocacy before lapsing into breach fatigue. These differences highlight that public apathy is not uniform, but shaped by generational memory, cultural norms, and historical experiences with governance. The novelty of this study lies in providing one of the first empirically grounded, generational analyses of digital insecurity in a Global South context. It reframes apathy not as disengagement but as an affective response to repeated institutional failure. Policy reforms—generationally targeted digital literacy initiatives, enforceable sanctions for public sector breaches, mandatory disclosure, and independent oversight—are essential to rebuild trust and counteract the emotional governance shaping Indonesia’s digital landscape.